GI Hemorrhage From an Arterio-Enteric Fistula From a Failed Pancreas Allograft. Issue 7 (11th July 2022) - David, Robin; Trieu, Judy A.; Shokoohi, Susanne
ABSTRACT: Arterio-enteric fistulas involving pancreas allograft are rare complications of transplantation that manifest as gastrointestinal bleeding. We discuss the case of a 34-year-old patient with failed pancreas transplant who presented with recurrent sentinel bleeding before catastrophic hemorrhage. Multiple endoscopies did not identify the source of bleeding, and subsequent angiography demonstrated a fistulous connection between the transplanted pancreatic artery and the small bowel. A stent graft was placed with immediate stabilization. We provide a review of the literature and discuss the clinical manifestations, diagnosis, and management of arterio-enteric fistulas to highlight the importance of early recognition and intervention in preventing life-threatening bleeding.